Scale dependence of structure-function relationship in the emphysematous mouse lung - Sato, Susumu; Bartolák-Suki, Erzsébet; Parameswaran, Harikrishnan; Hamakawa, Hiroshi; Suki, Béla (Frontiers in Physiology, 2015)
The purpose of this study was to determine how the initial distribution of elastase in mouse lungs determines the time course of tissue destruction and how structural heterogeneity at different spatial scales influences lung function. We evaluated lung function and alveolar structure in normal and emphysematous C57BL/6 mice at 2 and 21 days following orotracheal treatment with porcine pancreatic elastase (PPE). Initial distribution of elastase 1 h after treatment was assessed using red fluorescently labeled PPE (f-PPE) by laser scanning confocal microscopy. From measured input impedance of the respiratory system, the global lung compliance, and the variability of regional compliance were obtained. Lungs were fixed and equivalent airspace diameters were measured in 4 lobes of the right lung and 3 regions of the left lung. At day 2 and day 21, the mean airspace diameter of each region was significantly enlarged which was accompanied by an increased inter-regional heterogeneity. The deposition of f-PPE on day 0 was much more heterogeneous than the inter-regional diameters at both day 2 and day 21 and, at day 21, this reached statistical significance (p<0.05). Microscale heterogeneity characterized by the overall variability of airspace diameters correlated significantly better with compliance than macroscale or inter-regional heterogeneity. Furthermore, while the spatial distribution of the inflammatory response does not seem to follow that of the elastase deposition, it correlates with the strongest regional determinant of lung function. These results may help interpret lung function decline in terms of structural deterioration in human patients with emphysema.